The honest thief: a qualitative study exploring the ethics of clandestine intelligence collection in a statutory environment - Corbett,Trevor R (Department of Public Law, 2019)
Researchers studying intelligence ethics have rarely had access to the insight of serving intelligence practitioners. In this study, a small number of practitioners were sampled in an attempt to gain an understanding of the techniques they use to make sense of the ethically questionable tasks they are required to undertake within the legal framework of the institution of intelligence. The researcher argued that intelligence practitioners may use some of the neutralization techniques found in criminological and psychological models in order to remain effective in an environment which places their personal ethical framework at risk of compromise. In some aspects, themes seemed to correspond with the Rational Choice Theory of Cornish and Clarke (1986), the Neutralization Theory of Sykes and Matza (1957) and the Cognitive Dissonance theory of Festinger (1957). Themes were categorised under two primary headings: the institutional framework and a conceptual and theoretical perspective of ethics in relation to intelligence practice. It could be argued that intelligence ethics studies may be entrenched in the overarching fields of philosophy, criminology and psychology as they all offer useful explanations of how deviant behaviour is understood and justified by individuals. A combination of factors played into how they made ethical decisions and how they justified (or did not) these decisions. Findings suggested a combination of institutional frameworks (deontologically derived rules predetermined by the institution) and personal ethical frameworks (derived by each individual participant’s family, religion etc) were key in creating a working ethical framework (intertwining the former and the latter) which allowed/justified them in making ethical decisions which they considered vital to a nation-state’s survival.